Diagnosis experiences from 50 hepatitis B patients in Chongqing, China: a qualitative study - Xiangxi Zhou; Fan Zhang; Yongping Ao; Chunli Lu; Tingting Li; Xianglong Xu; Huan Zeng (BMC, 2021)
Abstract Background The aim of this study was to provide recommendations for reducing the impact of hepatitis B infection on patients with chronic hepatitis B by describing their experiences during the diagnosis process. Methods We conducted face-to-face interviews with 50 hepatitis B patients recruited by convenient sampling from an infectious diseases department of a teaching hospital in Chongqing, China from July to August 2019. Thematic analysis framework included interviewees' social demographic characteristics, diagnosis approach, signs and symptoms before diagnosis, feelings after diagnosis, and doctor's instructions. Results Most patients first detected hepatitis B through various types of physical examinations when the patients were asymptomatic or had only mild symptoms. Most patients were shocked, scared, or overwhelmed when they were diagnosed with hepatitis B. They were able to remember the doctor's instructions about maintaining a healthy lifestyle, but not impressed by the doctor's advice about regular follow-up liver function tests. The lack of regular follow-up has caused irreversible damage to some patients. Conclusions Most patients are passively diagnosed with hepatitis B due to their lack of awareness on active hepatitis B prevention. Patients need professional mental health care to overcome the negative emotions that following the diagnosis. Physicians' instruction should emphasize the importance of regular follow-up liver function tests in addition to a healthy lifestyle.